FINANCIAL INCLUSION THROUGH FINTECH PLATFORMS: OPPORTUNITIES AND CHALLENGES IN INDONESIA - Maya Ariyanti; Ucu Supriatna; Faisal Matriadi (Journal of Economics, Accounting, Business, Management, Engineering and Society, 2024)
Background: Indonesia faces persistent financial exclusion despite economic growth, with over 100 million adults lacking formal financial access. Aims: This research investigates fintech contributions to financial inclusion in Indonesia. Method: Mixed-methods with survey (n=500) and interviews across urban/rural Indonesia. Results: Digital payments show 78% adoption; digital lending reaches 42% of previously unbanked. Key barriers include digital literacy (65%), internet access (52%), and trust (48%). Government support correlates with 2.3x higher adoption. Contribution: Provides evidence for fintech-driven inclusion in emerging markets, informing policy and platform development.